2020
DOI: 10.1016/j.wear.2020.203238
|View full text |Cite
|
Sign up to set email alerts
|

Study on the characterisation of the PTFE transfer film and the dimensional designing of surface texturing in a dry-lubricated bearing system

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…A reduction of wear debris' size and fewer cracks were observed, both of which likely contributed to the superior wear performance. The effects of area density and depth on wear were also reported in a recent study of Ding et al [182]. They observed that shallow dimples with low area densities demonstrated enhanced film formation ability, thus compensating for negative edge effects that increase abrasion (Figure 11 In an innovative study, Wang et al recently electro-deposited MoS2/PTFE mixtures (PTFE content between 0 and 20 wt.-%) in textures fabricated on a laser-cladded, wear-resistant Fealloy [190].…”
Section: Ptfe and Surface Texturessupporting
confidence: 70%
See 2 more Smart Citations
“…A reduction of wear debris' size and fewer cracks were observed, both of which likely contributed to the superior wear performance. The effects of area density and depth on wear were also reported in a recent study of Ding et al [182]. They observed that shallow dimples with low area densities demonstrated enhanced film formation ability, thus compensating for negative edge effects that increase abrasion (Figure 11 In an innovative study, Wang et al recently electro-deposited MoS2/PTFE mixtures (PTFE content between 0 and 20 wt.-%) in textures fabricated on a laser-cladded, wear-resistant Fealloy [190].…”
Section: Ptfe and Surface Texturessupporting
confidence: 70%
“…Most of these employed hard textured substrates such as stainless steel [179][180][181][182][183], bronze [184][185][186], silicon [187] or laminated ceramics [188,189], which were rubbing against an untextured PTFE nano-composite. Surface textures were mainly produced by LST using lasers with pulse durations ranging from micro- [179,181,[184][185][186] and nano- [188,189] to pico- [182] and femtoseconds [180,187]. Regarding the geometry of the textures, research effort has focused on dimples [179, 181-183, 185, 186, 188, 189], unidirectional grooves [180], grid-like textures, and circumferentially or radially aligned grooves [184].…”
Section: Ptfe and Surface Texturesmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of the transfer film is affected by the physical properties of the counter surface. For instance, the average roughness [11] or surface texturing [12] can have a great impact on the formation of the transfer film. There is a general consensus about the observation that in sliding PTFE/steel contacts the friction coefficient decreases while the wear rate increases with increasing contact pressure [9,10,13].…”
Section: Introductionmentioning
confidence: 99%
“…Figure19. New seal fracture surface with thin layer separating lip coating from remaining seal material.…”
mentioning
confidence: 99%